Animal‐related facial fractures in South Australia. Issue 5 (3rd March 2021) - Diab, Jason; H. Moore, Mark
Abstract: Background: Animal‐related facial fractures can affect livelihoods impacting the hard and soft tissues of the face. Animal husbandry and recreational sports have close relationships with animals, which can lead to injuries equivalent to those of road traffic accidents and assaults. Our aim is to describe epidemiological trends of animal‐related facial fractures in the paediatric and adult age group across South Australia. Methods: A retrospective review from January 2012 to January 2017 at the Women and Children's Hospital and Royal Adelaide Hospital in Adelaide. All animal‐related injuries that attended or were referred to the unit were included in this study. Results: There were 50 patients who presented with an animal‐related facial fracture. There was an equal distribution of males to females with horses as the most common animal to cause injury from kicking. The orbit and orbitozygomatic fracture equally represented the most common type of facial fracture with 38% of all cases having an associated injury. The operative rate was 56% with four post‐operative complications. There were differences between males and females for season, post‐operative complications and length of stay ( P < 0.05). Females, multiple fractures and associated injuries were independently associated with increased length of stay ( P = 0.001). Conclusions: Female adolescents and young women involved with horses were more likely to have facial fractures with associated injuries, post‐operative complications and an extended length of stay compared to males. Educational awareness for trainees about interdisciplinary care and prevention strategies for patients are key to better understanding and managing facial trauma. Abstract : Comparison of horse and non‐horse‐related facial fractures. ( ), Horse; ( ), non‐horse.